DESIGN, DEVELOPMENT AND TO FORMULATE ANTIMICROBIAL GEL OF TOONA CILIATA ROEM. LEAVES AND FICUS BENGALENSIS LINN. STEM BARK. - Singh, Satnam (Innovare Journal of Ayurvedic Sciences, 2014)
The aim of the present study is to investigate the antimicrobial property and to formulate an antimicrobial Gel of Toona ciliata Roem. leaves and Ficus bengalensis Linn. stem bark. The antimicrobial activity was evaluated by using agar cup plate method and minimum inhibitory concentration against four microorganisms was determined. Soxhlet apparatus was used for successive extraction using solvents - petroleum ether, chloroform, methanol and water. And Â to formulate polyherbal antimicrobial gel carbopol 940 was used as gelling agent. Petroleum ether extract was found to be the most effective of the three extracts. The antimicrobial activity was observed against the gram positive bacteria Staphylococcus aureus, Bacillus subtilis and gram negative bacteria Pseudomonas aeruginosa; and the fungus Candida albicans. The minimum inhibitory concentration (MIC) of Toona ciliata petroleum ether extract ranged from 40mg/ml-50 mg/ml and that of Ficus bengalensis petroleum ether extract from 10mg/ml-16 mg/ml at which selected organisms showed inhibition. Then using a range of concentrations of carbopol 940 different gel formulations were formulated with petroleum ether extracts of both plants and tested for their antimicrobial potential. Out of these F2 and F6 formulation were combined in different ratios Â and one with ratio 3:7 was further tested for antimicrobial activity by Agar Cup method. It was found that ratio 3:7 have synergistic effect and possessed considerable antimicrobial activity and may serve as promising antimicrobial gel formulation. From this study, it can be concluded that Toona ciliata Roem. leaves and Ficus bengalensis Linn. stem bark exhibited antimicrobial activities against selected microorganisms. Keywords: Toona ciliata Roem., Ficus bengalensis Linn., Antimicrobial activity, In-vitro diffusion study, Agar cup plate method, MIC, Carbopol 940, Hydrogel, Cold method, Topical.